Ingestion and effects of cerium oxide nanoparticles on Spodoptera frugiperda (Lepidoptera: Noctuidae). (15th June 2021) - Castro, Bárbara M.M.; Santos-Rasera, Joyce R.; Alves, Dejane S.; Marucci, Rosangela C.; Carvalho, Geraldo A.; Carvalho, Hudson W.P.
Abstract: The objective of this study was to evaluate the biological and nutritional characteristics of Spodoptera frugiperda (Lepidoptera: Noctuidae), an arthropod pest widely distributed in agricultural regions, after exposure to nano-CeO2 via an artificial diet and to investigate the presence of cerium in the body of this insect through X-ray fluorescence mapping. Nano-CeO2, micro-CeO2, and Ce(NO3 )3 were incorporated into the diet (0.1, 1, 10, and 100 mg of Ce L −1 ). Cerium was detected in caterpillars fed with diets containing nano-CeO2 (1, 10 and 100 mg of Ce L −1 ), micro-CeO2 and Ce(NO3 )3, and in feces of caterpillars from the first generation fed diets with nano-CeO2 at 100 mg of Ce L −1 as well. The results indicate that nano-CeO2 caused negative effects on S. frugiperda . After it was consumed by the caterpillars, the nano-CeO2 reduced up to 4.8% of the pupal weight and 60% of egg viability. Unlike what occurred with micro-CeO2 and Ce(NO3 )3, nano-CeO2 negatively affected nutritional parameters of this insect, as consumption rate two times higher, increase of up to 80.8% of relative metabolic rate, reduction of up to 42.3% efficiency of conversion of ingested and 47.2% of digested food, and increase of up to 1.7% of metabolic cost and 8.7% of apparent digestibility. Cerium caused 6.8–16.9% pupal weight reduction in second generation specimens, even without the caterpillars having contact with the cerium via artificial diet. The results show the importance of new ecotoxicological studies with nano-CeO2 for S. frugiperda in semi-field and field conditions to confirm the toxicity. Graphical abstract: Image 1 Highlights: Nano-CeO2 reduced up to 4.8% the pupal weight of S. frugiperda . Nano-CeO2 reduced by 60% the egg viability of S. frugiperda . Nano-CeO2 increases of up to 1.77% the metabolic cost and 8.70% the digestibility of S. frugiperda . Nano-CeO2 exhibits transgenerational effects on S. frugiperda .